SIRAH LEARNING MOBILE APPLICATION FOR KAFA PRIMARY SCHOOL STUDENTS: A PRELIMINARY STUDY - Siti Fatimah Mohd Rum; Nurulhuda Basri; Azlin Dahlan (Journal of Islamic, Social, Economics and Development, 2022)
Sirah is one of the Malaysian Islamic education systems for Ujian Penilaian Kelas KAFA (UPKK) subject compulsory for all primary students in Standard 5. Due to the Covid- 19 pandemic, teachers have to cancel most classes and opt for online classes. Thus, the biggest issue arose when the students found it challenging to focus on online lectures because they were in an undesigned classroom and would miss class if their internet connection was poor. In addition, they had difficulties memorizing the subjects if they were not appropriately engaged. As a result, this research offered a new learning technique utilizing the interactive Sirah learning mobile application. Students will read notes and take quizzes on three introductory topics in Sirah based on the KAFA syllabus. The ADDIE model was used to design and develop this mobile application, which runs on Android. Functionality testing results showed that this study achieved its requirements, and using SUS calculation, usability testing established a good score of 77.81%. In conclusion, this approach may enable students to learn more enjoyable and conveniently without worrying about missing classes.